GAMBARAN DAYA TAHAN AEROBIK (VO2MAX) PADA ATLET DAYUNG KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) PROVINSI RIAU TAHUN 2015 - Yulia Yulia Rahmawati Rahmawati; Yanti Ernalia; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACT Rowing is a sport featured Indonesian National Sports Committee Riau Province which require considerable force. Achieve good performance need a good physical condition. Aerobic endurance (VO2max) has contributed in aerobic endurance. VO2max value the better the athlete, the more fit physical health conditions. The purpose of this study was to know the description of aerobic endurance (VO2max) on rower Indonesian National Sport Committee (KONI) Riau province in 2015. This research method is a descriptive cross-sectional with total sampling technique. VO2max values obtained from the results of physical tests using balke test. The study was conducted on 57 respondents consisting of 43 men and 14 women. Results of this study showed the male athletes as many as 24 people (55.8%) in the category of very poor, 13 (30.2%) very poor and 6 (14.0%) enough. Whereas in female athletes earned 8 (57.1%) in the poor category and 6 (42.9%) very poor. Keywords: aerobic endurance (VO2max), rower men and women, Indonesian national sport committee